Influence of wood physical properties on charcoal from Eucalyptus spp - Andrade, Fernando Wallase Carvalho [UNESP]; Filho, Mario Tomazello; Moutinho, Victor Hugo Pereira (FapUNIFESP (SciELO), 2018)
The use of wood in the form of charcoal for energy production, has great economic importance in Brazil. In this context, the study of variables and mechanisms that affect charcoal quality is essential. The present study aimed to verify the influence of some physical properties of Eucalyptus wood on the quality and yield of the produced bioreducer. We used three commercial Eucalyptus clones, cultivated for use in the steel industry, determining wood density and shrinkage, density and immediate chemistry of the charcoal produced and the charcoal gravimetric yield. The data was submitted to Pearson's correlation analysis. Correlations between wood density and apparent charcoal density as well as charcoal ash content were observed. All clones presented characteristics suitable for the production of charcoal for the steel industry, with emphasis on the hybrid E. urophylla x E. grandis.
Keywords: Charcoal properties; E. urophylla x E. grandis; Steel charcoal; Wood density